Comparação da flexibilidade, qualidade de vida e capacidade funcional entre idosos ativos e sedentários dos meios urbano e rural - Navega, Marcelo Tavella [UNESP]; Miguel, Tais Pereira [UNESP]; Del-Masso, Maria Candida Soares [UNESP] (My University, 2011)
Introduction:The regular practice of physical activity is being used as a therapeutic resource to the elderly population, with the objective of reduction of the losses provoked by the growing old process. The home place (urban or rural) is still little explored in literature about your infl uence in the physical capacity of the elderly people. Objective: The aim of this study was to value and compare the quality of life, motion and functional capacity between physically active and sedentary elderly people, residents in the urban and rural area. Methods: Sixty people with age above 60 years old were valued, 20 physically active residents in the urban area (66,5 ± 4,32 years), 20 sedentary residents in the urban area (68,8± 7,24 years), 10 physically active residents in the rural area (64,4±2,46 years) and 10 sedentary residents in the rural area (68±5,78 years). It was realized the evaluation of the fl exibility (previous fl exon of the trunk), mobility (timed up and go test), a six-minute walk test and answered a quality of life’s questionnaire SF-36. To compare the results obtained by the two groups was used the Kruskal-Wallis test, and the signifi cant presence of the test was performed post hoc Newman-Keuls. The level of signifi cance used in statistical analysis was 5% (p<0,05).Results: It was observed that the physically active elderly people obtaine better performance on the six-minutes walk test. It wasn’t found difference in the mobility among the groups. In relation to the quality of life, the elderly residents in the rural area, were better in the component Vitally. In relation to the fl exibility the elderly residents in the urban area obtained the best results. So, we can conclude that the practice of physical activity realized by the volunteers contributed to a better functional capacity, observed by the biggest distance gone through on the walk test. The rural home place positively infl uenced the vitality control, while the fl exibility was worse presented in these elderly people.

Introdução: A prática regular de atividade física vem sendo utilizada como recurso terapêutico para população idosa, com objetivo de redução das perdas desencadeadas pelo processo de envelhecimento. A área de moradia (urbana ou rural) ainda é pouco explorada na literatura sobre sua infl uência na capacidade física dos idosos. Objetivos: avaliar e comparar a qualidade de vida, mobilidade e capacidade funcional entre idosos ativos fi sicamente e sedentários, moradores da zona urbana e rural. Métodos: Foram avaliados 60 indivíduos com idade acima de 60 anos, sendo 20 ativos fi - sicamente moradores da zona urbana (66,5 ±4,32 anos), 20 sedentários moradores da zona urbana (68,8±7,24 anos), 10 ativos fi sicamente moradores da zona rural (64,4±2,46 anos) e 10 sedentários moradores da zona rural (68,6±5,78 anos). Foram realizadas as avaliações da fl exibilidade, mobilidade, teste de caminhada de seis minutos e respondido o questionário de qualidade de vida SF-36. Para comparar os resultados foi utilizado o teste Kruskal-Wallis e o post hoc Newman-Keuls (p< 0,05). Resultados: foi observado que os idosos ativos fi sicamente obtiveram melhor desempenho no teste de caminhada. Não foi encontrada diferença na mobilidade entre os grupos. Em relação à qualidade de vida, os idosos moradores da zona rural mostraram-se melhores no componente Vitalidade. Em relação à fl exibilidade os idosos moradores da zona urbana obtiveram melhores resultados. Conclusões: a prática de atividade física realizada pelos voluntários contribuiu para uma melhor capacidade funcional. A área de moradia rural infl uenciou positivamente o domínio vitalidade, enquanto a fl exibilidade mostrou-se pior nesses idosos.
Compare between physically active and sedentary elderly people, residents in the urban and rural area
Keywords: idoso; envelhecimento; Flexibilidade